Rituximab Treatment and Long-term Outcome of Patients With Autoimmune Encephalitis: Real-world Evidence From the GENERATE Registry. - Thaler, Franziska S.; Zimmermann, Luise; Kammermeier, Stefan; Strippel, Christine; Ringelstein, Marius; Kraft, Andrea; Suhs, Kurt-Wolfram; Wickel, Jonathan; Geis, Christian; Markewitz, Robert; Urbanek, Christian; Sommer, Claudia; et al. (Neurology, Neuroimmunology and Neuroinflammation, 2021)
BACKGROUND AND OBJECTIVES: To determine the real-world use of rituximab in autoimmune encephalitis (AE) and to correlate rituximab treatment with the long-term outcome. METHODS: Patients with NMDA receptor (NMDAR)-AE, leucine-rich glioma-inactivated-1 (LGI1)- AE, contactin-associated protein-like-2 (CASPR2)-AE, or glutamic acid decarboxylase 65 (GAD65) disease from the GErman Network for Research on AuToimmune Encephalitis who had received at least 1 rituximab dose and a control cohort of non-rituximab-treated patients were analyzed retrospectively. RESULTS: Of the 358 patients, 163 (46%) received rituximab (NMDAR-AE: 57%, CASPR2-AE: 44%, LGI1-AE: 43%, and GAD65 disease: 37%). Rituximab treatment was initiated significantly earlier in NMDAR- and LGI1-AE (median: 54 and 155 days from disease onset) compared with CASPR2-AE or GAD65 disease (median: 632 and 1,209 days). Modified Rankin Scale (mRS) scores improved significantly in patients with NMDAR-AE, both with and without rituximab treatment. Although being more severely affected at baseline, rituximab-treated patients with NMDAR-AE more frequently reached independent living (mRS score ≤2) (94% vs 88%). In LGI1-AE, rituximab-treated and nontreated patients improved, whereas in CASPR2-AE, only rituximab-treated patients improved significantly. No improvement was observed in patients with GAD65 disease. A significant reduction of the relapse rate was observed in rituximab-treated patients (5% vs 13%). Detection of NMDAR antibodies was significantly associated with mRS score improvement. A favorable outcome was also observed with early treatment initiation. DISCUSSION: We provide real-world data on immunosuppressive treatments with a focus on rituximab treatment for patients with AE in Germany. We suggest that early and short-term rituximab therapy might be an effective and safe treatment option in most patients with NMDAR-, LGI1-, and CASPR2-AE. CLASS OF EVIDENCE: This study provides Class IV evidence that rituximab is an effective treatment for some types of AE.
EVALuna2:472586